Pengembangan Modul Layanan Informasi Karir Berbasis Ensiklopedia Bergambar Untuk Pemahaman Karir - Vica Dwi Pratiwi Vica; Weni Kurnia Rahmawati; Noviana Mariatul Ulfa (Jurnal Consulenza : Jurnal Bimbingan Konseling dan Psikologi, 2023)
Career information service guidance is important for students because students are still confused about choosing a career. The purpose of this study was to produce a career information module media for class XI of the Accounting Department that students can use as a guide for career selection, and can be used as a guide for guidance and counseling teachers. This study uses 10 stages of the Borg & Gall (2021) model which are adjusted into 6 stages. Collecting data using interviews, questionnaires, and documentation. The product validation formula is used to obtain questionnaire results from media experts, material experts, and practitioner experts. The subjects of this study were students of class XI Accounting who were selected by random sampling. The number of research subjects was 10 respondents (small group test) and 5 validators (validation test). The results of the module practicality response questionnaire obtained a score of 92.6%. While media expert validation obtained 90.83% (very feasible), material expert validation obtained 92.5% (very feasible), practitioner expert validation results obtained 94% (very feasible) it can be concluded that the research results regarding the product being developed are acceptable and worth using. Keywords: Module;Career Information; Students